QADIYAH AL-ISTI'BAD FI SYI'R MUHAMMAD AL-FAYTURI - Arifin, Zamri; Arrabea, Emad Hamza M (Arabi : Journal of Arabic Studies, 2017)
The issue of slavery is one of the most important issues that have plagued mankind, both ancient and modern. The contemporary Arab poet Muhammad Miftah al-Fittouri was the first Arab poet to address this issue and to discuss the issues of African and Zenism in a qualitative and quantitative manner. Therefore, this study is aimed at presenting the efforts of the scholars of this issue in the poetry of this poet. The study revealed the intersections of the poetry with the components and manifestations of the issue of (slavery) and the different poetic stages, as demonstrated by the poet's poetic. The research concluded that the literary and monetary field lacked a systematic study of this issue, revealing its motives and artistic manifestations, and the various aspects of it emerge according to a modern scientific method.